Activation training facilitates gluteus maximus recruitment during weight-bearing strengthening exercises - Cannon, J.; Weithman, B. A.; Powers, C. M. (Journal of Electromyography and Kinesiology, 2022)
Given its tri-planar action at the hip, strengthening of gluteus maximus (GMAX) has been advocated as part of rehabilitation and injury prevention protocols for various musculoskeletal conditions. However, recruitment of GMAX during weight-bearing strengthening exercises can be challenging owing to the muscular redundancy at the hip for a given joint motion. The current study sought to determine if a 1-week activation program could result in greater GMAX recruitment during functional strengthening exercises. Pre- and post-training surface electromyography were collected from 12 healthy participants as they performed double- and single-leg squats. Between testing sessions, participants completed a GMAX activation training program consisting of isometric exercises with band resistance (twice per day for 7 days). Following the 1-week activation program, GMAX recruitment was found to increase by 57% during the double-leg squat (p = 0.005, Cohen`s r = 0.73) and 53% during the single-leg squat (p = 0.006, Cohen`s r = 0.70). Implementation of an initial GMAX activation program should be considered to facilitate neuromuscular adaptations that facilitate utilization of GMAX during hip strengthening exercises.